Onfarm testing of Mucuna and cowpea double cropping with maize in the Guinea savanna of Nigeria - Oyewole, B.; Carsky, R.J.; Schulz, S. (2000)
On-farm trials were conducted at Kaduna in the northern Guinea savanna of Nigeria in 1996 and 1997. The objective was to investigate the residual effects of Mucuna and cowpea grown during the first 2-3months of the season on subsequent maize yields, to elicit farmers' feedback on these cropping systems, and to assess their economic impact. Maize yields after Mucuna were 20-60% higher than after cowpea. However the cowpea-maize system produced additional cowpea grain while did not produce any edible grain. A partial budget analysis revealed that the Mucuna-maize system might be advantageous in environments where cowpea yields are very low but that with increased cowpea yields the cowpea-maize system tends to be more profitable. Farmers observed that Mucuna effectively suppressed weeds in the subsequent maize and appreciated its substantial residual effect. They complained that in this system Mucuna did not produce seed for replanting and the incorporation of the residues was difficult. A further follow up showed that the number farmers using Mucuna in that village decreased in 1998 and that they had stopped growing the crop in 1999. It therefore appears that the adoption potential of Mucuna as an early season crop is rather limited in this socioeconomic environment in which farmers already have a legume that provides a food and soil fertility benefit.